Tram accidents in the Soviet urban everyday life of the 1920s - Sidorchuk, Ilya Victorovich (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The article shows the scale of the problem of tram accidents in early Soviet cities, identifies its causes, proposed and implemented measures to eliminate them, and assesses their effectiveness. The main factors of the disasters were disregard for safety rules, mistakes of the tram drivers, a small number of tram cars and their poor quality. Despite a number of measures taken, the issue of creating a safe urban transport system could not be resolved in the unstable economic and social conditions of the 1920s.